The Resilience of Couples with Disabilities in Achieving a Sakinah Family in Palu City - Muh. Rezki; Suhri Hanafi; Nurkhaerah Nurkhaerah (State Islamic University Datokarama Palu, 2026)
This study examines the resilience of couples with disabilities in achieving a sakinah family in Palu City and identifies the factors that support and hinder this process. Using a qualitative socio-legal approach, data were collected through observation, structured interviews, and document analysis involving married couples with disabilities in Palu City. The findings reveal that couples with disabilities demonstrate strong family resilience despite facing physical limitations, social challenges, and economic pressures. Their resilience is reflected in their ability to adapt to adversity, maintain mutual support, foster effective communication, strengthen spiritual values, and cooperate in fulfilling family responsibilities. These capacities enable them to build harmonious family relationships and pursue the ideals of a sakinah family. Supporting factors include spousal support, family and community assistance, religious values, and participation in inclusive social networks. Conversely, limited religious knowledge, restricted employment opportunities, low educational attainment, and inadequate accessibility to public facilities constitute major obstacles. The study concludes that family resilience serves as a fundamental foundation for couples with disabilities in achieving a sakinah family, highlighting the importance of psychological, social, economic, and spiritual support in strengthening family well-being.